2008
DOI: 10.1177/031289620803300106
|View full text |Cite
|
Sign up to set email alerts
|

Cost-of-Capital Estimation and Capital-Budgeting Practice in Australia

Abstract: We use a sample survey to analyse the capital-budgeting practices of Australian listed companies. We find that NPV, IRR and Payback are the most popular evaluation techniques. Real options techniques have gained a toehold in capital budgeting but are not yet part of the mainstream. Discounting is typically by the weighted average cost of capital, assumed constant for the life of the project, and with the same discount rate across divisions. The WACC is usually based on target weights for debt and equity. The C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
1
18

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(63 citation statements)
references
References 17 publications
4
40
1
18
Order By: Relevance
“…Our results support G. Truong et al (2008), who concluded that, in Australia, projects were usually evaluated using the NPV, the IRR and the PP, and S. Verma et al (2009), with very similar results, but on the corporate practice in India. Our fi ndings slightly diff er from the fi nding of the study conducted by L. Dedi and S. Orsag (2007) in Croatian fi rms, who found out the following priority list of metrics: 1) the IRR (59%), 2) the PP (56%) and 3) the NPV (42%).…”
Section: Capital Budgeting Metricssupporting
confidence: 88%
See 1 more Smart Citation
“…Our results support G. Truong et al (2008), who concluded that, in Australia, projects were usually evaluated using the NPV, the IRR and the PP, and S. Verma et al (2009), with very similar results, but on the corporate practice in India. Our fi ndings slightly diff er from the fi nding of the study conducted by L. Dedi and S. Orsag (2007) in Croatian fi rms, who found out the following priority list of metrics: 1) the IRR (59%), 2) the PP (56%) and 3) the NPV (42%).…”
Section: Capital Budgeting Metricssupporting
confidence: 88%
“…The overall conclusion of the study was that practice signifi cantly deviates from theory, especially in the domain of the capital structure, but also in the domain of capital budgeting. After this study, a number of later studies sought to confi rm or deny the Graham-Harvey fi nding or to analyze the practice from new perspectives Sandahl & Sjögren, 2003;Brounen, De Jong & Koedijk, 2004;Dedi & Orsag, 2007;Truong, Partington & Peat, 2008;Verma, Gupta & Batra, 2009;Baker, Dutt a & Saadi, 2011;Correia, 2012;Andrés, Fuente & San Matin, 2014).…”
Section: Theoretical Background and Literature Overviewmentioning
confidence: 99%
“…Block (2003) Truong et al (2008) majoritariamente apontam o uso da estrutura de capital alvo. Contrariando essa linha, a Tabela 6 indica que o uso da estrutura de capital corrente é a preferida por 64% dos respondentes, enquanto que apenas 22% consideram adequado o uso da estrutura de capital alvo.…”
Section: Referencial Empíricounclassified
“…Essa prática não difere muito dos trabalhos americanos de Bruner et al (1998) e Brotherson et al (2013) que identificam a prática de revisão anual, respectivamente, de 37% e 50%. Trinta e dois por cento das empresas australianas revisam o cálculo do WACC anualmente, enquanto que 30% o fazem sempre que há um novo projeto, segundo Truong et al (2008).…”
Section: Q10 Qual é a Composição Da Dívida Considerada No Custo De Cunclassified
See 1 more Smart Citation